Effect of Time and Temperature of Air Jet on the Mechanical and Biological Behavior of a Universal Adhesive System - Zimmer, R.; Leite, M. L. [UNESP]; Costa, C. A. de Souza [UNESP]; Hebling, J. [UNESP]; Anovazzi, G. [UNESP]; Klein, C. A.; Hosaka, K.; Reston, E. D. (Operative Dentistry, 2022)
OBJECTIVES: To evaluate the influence of heat application on the degree of conversion (DC) of the 3M Single Bond Universal Adhesive System, as well as its transdentinal cytotoxicity and microtensile bond strength to dentin. METHODS: Experimental groups were established according to the time and temperature of the air jet: G1: 5 seconds-25°C; G2: 10 seconds-25°C; G3: 20 seconds-25°C; G4: 5 seconds-50°C; G5: 10 seconds-50°C; G6: 20 seconds-50°C. In control group (G7), no treatment was performed. The DC was assessed using the Fourier transform infrared spectroscopy-attenuated total reflectance (FTIR-ATR) technique. For the transdentinal cytotoxicity test, dentin discs fitted in artificial pulp chambers (APC) received the application of the adhesive system and the air jets. For the microtensile bond strength, healthy molars were restored and submitted to the microtensile test after 24 hours and 6 months, respectively. RESULTS: Significant reduction in viability of Mouse Dental Papilla Cell-23 (MDPC-23), which exhibited morphological changes, was observed in all experimental groups compared to control (p<0.05). Although all tested protocols resulted in transdentinal diffusion of 2-hydroxyethyl methacrylate (HEMA), the group G6 presented the highest degree of monomeric conversion and the lowest cytotoxic effect, with higher dentin bond strength values in comparison to group G1 (p<0.05). CONCLUSIONS: Applying an air blast at 50°C for 20 seconds increases the DC and microtensile bond strength of the 3M Single Bond Universal Adhesive System to dentin, as well as reduces the transdentinal cytotoxicity of the material to pulp cells.